Determining Layer Oil Shale as New Alternative Energy Sources Using Core Analysis and Well Log Method - S Mulyanto, Bagus; Dewanto, Ordas; Rizky, Sri (International Journal of Engineering and Technology, 2018)
Oil shale is a type of shale containing organic material is not yet mature. When heated to a certain temperature, the organic content to mature so that it can produce petroleum. Exploration with a reliable method to energy sources of the future needs to be done, because it has a particularly important role in the context of the national energy supply security in the future.Â Oil deposits in shale oil is quite high, estimated as relatively large reserves spread across several regions of Indonesia. To determine the content of oil shale in the basin necessary to evaluate the condition of the reservoir, by determining and analyzing the reservoir parameters. Determination and analysis of reservoir parameters is done by two methods, namely core analysis in the laboratory and log interpretation in the field. Â Â Determination of oil-bearing layer in the wells is performed quantitatively which is based on the value HTTI=14.20-75.30 ï€¨Â´103 cal cm-3)and Ro=0.70-2.17 (%). Â Further is qualitatively to determine layer containing shale (oil shale). Â First look at the layers of shale from the high GR value and then their separation sonic and resistivity in the shale layer. Â A layer of oil shale wells BG-6 is present at a depth of 1637-1687 meters. Â BGS-1 wells at a depth of 2025-2062, 2100-2125, 2175-2200, 2275-2310 meters. Â BGS-2 wells at a depth of 2025-2045, 2138-2160, 2275-2295, 2380-2405 meters. Â BGS-3 wells at a depth of 2150-2165, 2212-2225 meters. Â While the BGS-4 wells at a depth of 2175-2187.5, 2212.5-2245, 2300-2312.5, 2350-2388 meters.Â Â